When Should the Customer Really be King? On the Optimum Level of Salesperson Customer Orientation in Sales Encounters - Homburg, Christian; Müller, Michael; Klarmann, Martin (Journal of Marketing, 2011)
In today's age of relational selling, a key challenge for salespeople is to determine the degree to which their customer-oriented behaviors drive sales performance. Therefore, this study analyzes whether a salesperson's customer orientation in sales encounters has an optimum level with regard to sales performance and customer attitudes. Using triadic data from a cross-industry survey of 56 sales managers, 195 sales representatives, and 538 customers, the authors provide strong empirical support for a curvilinear, inverted U-shaped effect of a salesperson's customer orientation on sales performance, whereas the effect of customer orientation on customer attitudes is continuously positive. Moreover, the findings reveal that the optimum level of customer orientation with regard to sales performance is higher for salespeople selling individualized products, in firms pursuing a premium price strategy, and in markets with a high degree of competitive intensity.